Optimización de perforación y voladura reduciendo el diámetro de perforación de 36mm a 32mm y usando fanel de micro-retardo en cr- se1 nv-2670 de ecm marose s.a.c. – cia. poderosa s.a. - Cruzado de la Cruz, Wilson Ronald (2018)
This work gives an account of a diagnosis and proposal of improvement of the current standards of blasting in CR-SE1, NV-2670 of section 2.50m * 2.70m of CIA Poderosa SA, ECM Marose SAC. The central theme is the reduction of the perforation diameter and the use of micro retardation fanels and how these influence the blasting results. The methodology applied for this evaluation was: the first, with respect to the analysis of the initial state of blasting with the current design, where the results were quantified as fragmentation, direct costs and behavior of the vibrations through the rock mass and its effect on the contour, and the second related to the proposal and implementation of improvements to the initial design, such as the reduction of the diameter of perforation, decrease of the length of load, use of load of low power in all the bores of contour and use of Faneles of the MS series. Based on the final result of this work, a proposal was made to improve the design of Drilling and Blasting in CR-SE1, from which results such as: Less damage to the contour of the excavation, reflected in the reduction of over excavation from 24.6% to 10.6%; more uniform fragmentation with P80 = 12.42cm; reduction of explosive consumption, which is reflected in the load factor, which decreases from 24.03kg / m to 21.58kg / m and decrease in the direct costs of drilling and blasting of S /. 743.45 / m to S /. 687.76 / m (reduction by 7.5% percentage points). Based on what has been achieved in this work, it is recommended to adapt the new design in all the fronts of progress and continue with the improvement of the Drilling and Blasting to obtain a global optimization in these processes.